Chronic interleukin-6 mediated neuroinflammation decreases anxiety, and impaires spatial memory in aged female mice - Wagnon, Ingrid Marguerite; Jabur, Lillian Jocelyn; Niedermayer, Garry; Münch, Gerald; Karl, Tim; Chesworth, Rose; Gyengesi, Erika (Frontiers in Neuroscience, 2023)
Introduction Neuroinflammation is a common feature of many psychiatric disorders as well as a common underlying mechanism of neurodegenerative diseases. Sex has been shown to strongly influence the development as well as the clinical expression of these pathologies. However, there is still a neglect regarding the consideration of sex effects in rodent experiments, and a substantial underrepresentation of females in studies. This work set out to expand our knowledge of neuroinflammatory mechanisms in female mice, at both a behavioral and molecular level. Methods This study used GFAP-IL6 mice, a model of chronic neuroinflammation, in which interleukin-6 (IL6) is overexpressed in the central nervous system under the control of the glial fibrillary acidic protein (GFAP) promoter. We evaluated aged (11-15-month-old) wild type-like (WT) and GFAP-IL6 female mice in behavioral tests assessing anxiety (elevated plus-maze, EPM, Light/dark box), and spatial learning and memory (Y-maze, YM and Barnes Maze, BM) and associative learning (fear conditioning, FC). We also examined gene expression of markers linked to neuroinflammation, neurodegeneration and neurotransmission via RT-qPCR in brain regions involved in motor control, anxiety, learning and memory. Results Female GFAP-IL6 mice exhibited reduced anxiety-like behavior in the EPM, and hypolocomotion in the light-dark test and EPM. Short-term memory impairment was evident in the YM but associative learning in FC was intact in GFAP-IL6 mice, suggesting domain-specific cognitive deficits in female GFAP-IL6 mice. In the BM, all mice showed intact learning and memory, but GFAP-IL6 mice exhibited higher latencies to enter the escape hole than WT mice. We analyzed the search strategy and found differences in the way GFAP-IL6 mice searched for the escape hole compared to WTs. RT-qPCR showed increased mRNA levels for molecules involved in pro-inflammatory pathways in the cerebellum, motor cortex, hippocampus, and amygdala in GFAP-IL6 mice. Of the regions examined, the cerebellum and the hippocampus showed upregulation of neuroinflammatory makers as well as dysregulation of glutamatergic and GABAergic neurotransmission gene expression in GFAP-IL6 mice compared to WTs. Conclusion In conclusion, we showed that chronic neuroinflammation via IL6 overexpression in aged female mice led to a less anxious-like phenotype, hypolocomotion and impaired intermediate-term spatial learning and memory in the YM.